2011
DOI: 10.1159/000330935
|View full text |Cite
|
Sign up to set email alerts
|

Western and Chinese Medicine in Oncology and Hematology

Abstract: Based on a conclusive theoretical background, both Western and Chinese Medicine have developed diagnostic and therapeutic procedures which lead to reproducible treatment results. Whilst Western Medicine focuses on a most precise diagnosis of tumor histology and the extend of dissemination, Chinese Medicine has developed tools for a functional diagnoses of disturbed body functions. And as Western Medicine aims at producing most specific targeted drugs, Chinese Medicine intends to stabilize disturbed body functi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 25 publications
0
3
0
1
Order By: Relevance
“…Long-term historical experiences show that the cooperation of TCM and western medicine may be more efficient for the cure and prevention of disease than each of them separately. Numerous studies reported the potential benefits of combined TCM and western medicine in improving tumor prognosis, reducing adverse reactions, and enhancing life quality (8)(9)(10)(11)(12). Recent clinical evidence indicates that the cooperation of Chinese patent medicines (CPMs) and DEX had a good effect on lowing cardiotoxicity and improving the anti-tumor efficiency of anthracyclines (13).…”
Section: Introductionmentioning
confidence: 99%
“…Long-term historical experiences show that the cooperation of TCM and western medicine may be more efficient for the cure and prevention of disease than each of them separately. Numerous studies reported the potential benefits of combined TCM and western medicine in improving tumor prognosis, reducing adverse reactions, and enhancing life quality (8)(9)(10)(11)(12). Recent clinical evidence indicates that the cooperation of Chinese patent medicines (CPMs) and DEX had a good effect on lowing cardiotoxicity and improving the anti-tumor efficiency of anthracyclines (13).…”
Section: Introductionmentioning
confidence: 99%
“…TCM originated in China 5,000 years ago, following a unique and complete theoretical framework and using its terminology of etiology and pathogenesis. According to National Center for Complementary and Alternative Medicine (NCCAM), TCM comprises a variety of practices, including Chinese pharmacologic medicine (herbal, animal and mineral medicine), acupuncture, moxibustion (burning a herb above the skin to apply heat to acupuncture points), tuina (Chinese therapeutic massage), dietary therapy, and Daoyin therapy (such as baduanjin, tai chi and Qigong, which are practices that combine specific movements or postures, coordinated breathing, and mental focus) ( 1 , 2 ). WM is several hundred years old but has rapidly progressed due to the advanced sciences and superb technologies.…”
Section: Introductionmentioning
confidence: 99%
“…The WM is widely accepted and applied relying on robust evidence from both clinical research and evidence-based medicine (identifying a question, searching for evidence, appraising the evidence, applying the evidence, and assessing the evidence), which leads to evidence-based clinical practice guidelines ( 3 ). Based on a conclusive theoretical background, Chinese and Western medicine have followed various routines to gain knowledge in diagnosing and treating specially defined diseases, leading to reproducible treatment results ( 1 ). WM and TCM follow various routines to gain knowledge in diagnosing and treating specially defined diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Abb. 2: Einsatz ergänzender Therapien, um einen möglichen Zusatznutzen zu erzielen ohne die Standardtherapie zu gefährden (adaptiert nach [11]).…”
unclassified